Augmented reality-based application design with rapid prototyping method to support practicum during the covid-19 pandemic - Abdullah 'Azzam; Muchamad Sugarindra; Qurtubi Qurtubi (Jurnal Sistem dan Manajemen Industri, 2022)
The COVID-19 pandemic that has occurred throughout the world has hampered the world of education in carrying out the learning process. It requires the world of education to make rapid changes to the concept of learning so that the results of the learning process remain following the curriculum. However, during a pandemic, students are forced to study from home. Of course, this limits the essence of the practicum, which has to be done in the laboratory because students need interaction activities with machines. Augmented reality (A.R.) is a technology that allows users to interact with virtual objects. In this study, the application design is carried out using the rapid prototyping method, which can quickly accommodate the application development process. This study proves that AR-based applications can increase the understanding of 58% of students about the use of lathe, milling and 3D printing machines.